URDC completes programme on Research Methodology Series 2007 - Wee, Chong Hui (Universiti Teknologi MARA, Sarawak, 2007)
The Unit for Research, Development and Commercialisation (URDC) of Universiti Teknologi MARA Sarawak (UiTM Sarawak) organised Module 3 of the Programme on Research Methodology on 19 April 2007. The module included research report writing and presentation. Assoc. Prof. Dr. Simon Faizal Hakim, Secretary of the Editorial Board of UiTM Sarawak's Jurnal Akademik, was the speaker for the session on research report writing. The session on presentation skills was handled by Assoc. Prof. Iris Syawe Seh Ling, one of the pioneering lecturers for URDC's Programme on Research Methodology series. The Programme on Research Methodology provides support for UiTM Sarawak's lecturers involved in research and writing.